Adolescent Digital Literacy Behavior On The Internet In Fulfilling Social Functionality (An Exploratory Study: Participants In Kompas Gramedia National Journalism) - Zein, Bhre Kirana; Darwis, Rudi Saprudin; Meilany, Lenny (UNIVERSITAS PAKUAN, 2022)
This study delves into the effects of Kompas Gramedia's digital literacy program, implemented through the Nationalism Journalism initiative, on the digital behavior and social functioning of teenagers in both offline and online contexts. Digital behavior encompasses actions and interactions in the digital realm, including online conduct, social media engagement, and technology utilization. Participants in the Nationalism Journalism program acquire significant digital literacy skills, empowering them to effectively fulfill their social roles, meet essential needs, and navigate challenges. Using an exploratory methodology, this research examines how Kompas Gramedia's digital literacy program influences the digital behaviors and social functioning of teenagers in both physical and online environments. The exploratory approach provides an initial, in-depth understanding of the research domain, identifies patterns, relationships, and potential phenomena, and assesses the extent to which digital literacy shapes both digital conduct and social functioning. The findings underscore the importance of nurturing digital literacy to enhance individual social functioning in the digital age, providing insights into constructive and ethical digital behaviors. The study's conclusions highlight the relevance of digital literacy in empowering individuals, especially teenagers, to make positive contributions to society, fulfill their basic needs, and engage wisely and ethically in both digital and physical settings.